Assessing the Duration of Unnecessary Hospitalization and Expenses in Older Individuals Suffering From Cerebral Vascular Accident in the Chronic Care Unit - Reza Nikookar; Shahram Ghaffari; Ahmad Ali Akbari Kamrani; Robab Sahaf; Manizhe Moghadam; Mahmod Reza Ghadimi (University of Social Welfare & Rehabilitation Sciences, 2015)
Objectives Health system costs are progressively increasing due to several factors such as the increase in the number of elderly population with chronic diseases. Therefore, the efficient use of limited financial and human resources are very important. We aimed to review unnecessary health care cost of elderly patients with stroke in acute care department of Fayyaz Bakhsh Hospital, Tehran and comparison with subacute care unit. Methods & Materials In this descriptive study, 51 patients admitted to the neurological unit of the Fayyaz Bakhsh Hospital were included. Results The average Length of Stay (LOS) was 8.3 days. 30 patients needed subacute care, which will result in average LOS in acute and subacute care of 6.2 and 2.1 days respectively (P<0.001). Moreover, the average cost of per patient and day hospitalization was 1.182.000 (ir.rials) and 1.416.000 (ir.rials), respectively, of which 17% were transferable to subacute care. Conclusion The results showed that 25% of LOS and 17% of the cost of the acute care to subacute care unit is transferable.